การประเมินพันธุกรรมและความสามารถในการรวมตัวของพันธุ์รักษาเพศผู้เป็นหมันของพริกหยวก - ขวัญดาว แก้วสมบัติ (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2017)
Cytoplasmic genic male sterility of chilies varieties CA1441-J-8 and CA1442 were identified by using a fertility scoring method. It was found that CA1441-J-8 and CA1442 were N msms or maintainers. Varieties CA1441-J-8 and CA1442 were crossed male parents. In 2010 and 2012, many F1 hybrids showed higher and significantly different than the female parents in yield, fruit weight per plant, fruit length, plant height, plant width, L, chroma and hue angle higher and significantly different than the female parents in fruit width, seeds number per plant were lower than. Many F1 hybrids showed higher and significantly different than the male parents in yield, fruit weight per plant, fruit width, plant height, plant width, L, chroma and hue angle higher and significantly different than the male parents in fruit length, seeds number per plant were lower than. Many F1 hybrids showed higher and significantly different than the commercial cultivars in yield, fruit weight per plant, fruit length, plant width, L, chroma and hue angle higher and significantly different than the commercial cultivars in fruit width, seeds number per plant were lower than. General combining ability of the maintainer CA1441-J-8 was positive and significantly different on L and chroma. The maintainer, CA1442 showed positive and significantly different of general combining abilities for hue angle. General combining ability of male parent CA1450-3-6 showed positive and significantly different on yield and L. The male parent, CA1447-4-19 showed positive and significantly different of general combining abilities for fruit length, L and chroma, The male parent, CA1448-5-13 showed positive and significantly different of general combining abilities for fruit length, hue angle and vitamin C. The male parent, CA1449-2-5 showed positive and significantly different of general combining abilities for hue angle, while CA1451-5-11 showed positive and significantly different of general combining abilities for chroma. The CA1441-J-8 were used as female parents, It was found that some F1 hybrids showed positive and significantly different of specific combining abilities for fruit weight, fruit thickness, fruit length, fruit width, seeds number per fruit, L, chroma, vitamin C and capsaicin. The CA1442 were used as female parents, It was found that some F1 hybrids showed positive and significantly different of specific combining abilities for fruit weight, fruit thickness, fruit length, fruit width, seeds number per fruit, plant width, L, hue angle, vitamin C and capsaicin. Many F1 hybrids exhibited positive significantly different heterosis for fruit number per plant, fruit weight per plant, fruit weight, fruit length, fruit width, L, chroma, hue angle, vitamin C. The maintainers, CA1441-J-8, CA1442 and the male parents, CA1447-4-19, CA1448-5-13 and CA1450-3-6 were suited to be used as parent for hybrid seed production. The F1 hybrids CA1441-J-8 × CA1450-3-6, CA1442 × CA1447-4-19, CA1442 × CA1448-5-13 and CA1442 × CA1450-3-6 could be used in development of a hybrid seed production.